2021
DOI: 10.5009/gnl20291
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Undifferentiated-Type Early Gastric Cancer with Positive Horizontal Margins after Endoscopic Resection

Abstract: Background/Aims: This study examined the long-term outcomes of undifferentiated-type early gastric cancer (UD EGC) with positive horizontal margins (HMs) after endoscopic resection (ER) and compared them between additional surgery and nonsurgical management. Methods:From 2005 to 2015, a total of 1,124 patients with UD EGC underwent ER at 18 tertiary hospitals in Korea. Of them, 92 patients with positive HMs as the only noncurative factor (n=25) or with both positive HMs and tumor size >2 cm (n=67) were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…Seven retrospective studies compared the recurrence rate of endoscopic treatments including re-ESD and APC, with gastrectomy or close observation [ 188 189 190 191 192 193 194 ]. The mean follow-up period for the 6 studies was 60 months, and these studies included both differentiated and undifferentiated cancers.…”
Section: Endoscopic Treatment ( Flowchart 2 )mentioning
confidence: 99%
See 1 more Smart Citation
“…Seven retrospective studies compared the recurrence rate of endoscopic treatments including re-ESD and APC, with gastrectomy or close observation [ 188 189 190 191 192 193 194 ]. The mean follow-up period for the 6 studies was 60 months, and these studies included both differentiated and undifferentiated cancers.…”
Section: Endoscopic Treatment ( Flowchart 2 )mentioning
confidence: 99%
“…Therefore, close observation could be considered a selective treatment option in cases of positive lateral margins in differentiated-type EGC. Recently, a retrospective study comparing gastrectomy and nonsurgical treatments (endoscopic treatment [6/52] and close observation [46/52]) in undifferentiated-type EGC has also been published [ 194 195 ]. The local recurrence rate was 0% in the surgical group and 21.2% (11/52) in the nonsurgical group, and the 5-year survival rate was 87.8% in the nonsurgical group, lower than the 95.0% in the surgical group, but without statistical significance.…”
Section: Endoscopic Treatment ( Flowchart 2 )mentioning
confidence: 99%
“…Previous research found that a cancer-positive horizontal margin (HM) more significant than 6 mm had been identified as an independent risk factor in the local GC recurrence[ 12 ]. However, subsequent studies have also shown that, without additional treatment, positive HM patients still have a comparable long-term prognosis and a low risk of lymphatic metastasis despite a non-low recurrence rate[ 13 ]. Furthermore, published research has found a higher GC recurrence risk in post-ESD patients with unevaluable or positive vertical margins than those with unevaluable or positive HM[ 14 ].…”
Section: Factors Associated With Gc Recurrence After Esdmentioning
confidence: 99%
“…In last issue of Gut and Liver, Yang et al 9 conducted an external validation of the eCura system for UD EGC using a large number of cases, and their study findings are reported herein. The authors collected data from 634 patients with noncurative endoscopic resection, of whom 270 underwent radical surgery and 364 received no additional treatment, from 18 institutions in Korea.…”
Section: 2023mentioning
confidence: 99%